Perlindungan Hukum Bagi Pengemudi Online Yang Mengalami Kerugian Akibat Orderan Fiktif Pada Layanan GrabFood - Faldi Rumasoreng; Theresia Louize Pesulima; Ronald Fadly Sopamena (PATTIMURA Law Study Review, 2023)
PT. Grab Indonesian collaborates with partners or drivers to enter into partnership agreements known in Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises. In accordance with Article 1 Number 13 of Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises confirms that the legal relationship between the two parties becomes a partnership relationship. But in this perspective, it cannot be said that the regulation can protect partners or drivers. This can be seen in fact there are still people who abuse the Grab application by making bookings that can harm partners or drivers if the booker does not pay in full for the ordered order using the COD (Cash On Delivery) transaction pattern or cash payment. This study used normative juridical research motede. This research is carried out by examining library materials or secondary data with conceptual and legislative approaches then the data is analyzed qualitatively and conclusions are drawn deductively, which is based on basic principles. The results of this study show that: 1) The legal consequences of fictitious order actions can be seen in two forms; First, from the form of unlawful acts. Where the perpetrator acts differently than required in terms of carrying out fictitious ordering actions by ordering food on GrabFood services. Second, from the form of default, where the perpetrator has committed acts of negligence and deliberate acts of fictitious ordering on GrabFood services. 2). The form of protection carried out by PT. Grab Indonesia one of them is providing forms of responsibility between the parties in the content of the partnership agreement in accordance with applicable laws and regulations. Then the responsibility of PT. Grab Indonesia as a business actor adheres to the principle of responsibility based on the element of error, where there is a fictitious order on the GrabFood service resulting in losses for the driver or drivers. So in order to compensate, the driver only gives.